A new Jaculistilus species of Mimarachnidae (Hemiptera: Fulgoromorpha) from mid-Cretaceous Kachin amber of northern Myanmar, with geometric morphometric analysis of the mimarachnid genera. (January 2023) - Jiang, Hui; Chen, Jun; Szwedo, Jacek
Abstract: Mimarachnidae is a Mesozoic planthopper family, with high palaeodiverisity at generic and species levels during Cretaceous. Herein, geometric morphometric analysis of mimarachinid forewings was executed. Our results of principal component and cluster analyses show that Dachibangus formosus and D. hui are morphologically distinct from the type species of Dachibangus . Therefore, Xiaochibangus gen. nov. is erected, and those two species are transferred to this new genus, resulting in new combinations – Xiaochibangus formosus comb. nov. and X. hui comb. nov. Besides, Jaculistilus xixuanae sp. nov., the second species of Jaculistilus with well-preserved 12 eyespots on tegmina, is described here from mid-Cretaceous Kachin amber of northern Myanmar, adding novel knowledge on the palaeodiversity of Mimarachnidae.